Catalase-mimetic gold nanoparticles inhibit the antagonistic action of Lactobacillus gasseri toward foodborne enteric pathogens in associative cultures. (3rd April 2019) - Zhu, Suqin; Zeng, Mingyong; Guo, Wei; Feng, Guangxin; Wu, Haohao
Abstract: Gold nanoparticles (AuNPs) have been previously shown to induce gut dysbiosis during colitis in mice, but the underlying mechanism is not clear yet. Here, we evaluated the effects of AuNPs (5 nm diameter, coated with tannic acid, polyvinylpyrrolidone or citrate) on H2 O2 accumulation and pathogen antagonization by an intestinal strain of Lactobacillus gasseri under aerobic cultural conditions. AuNPs (0.65 μg/mL) reduced over 50% of H2 O2 accumulation by L. gasseri, and significantly inhibited the antagonistic action of L. gasseri on growth of four foodborne enteric pathogens, i.e. Salmonella enterica serovar Typhimurium, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus in associative cultures.